The moderating effect of strength of manufacturer's brands on the relationship between retailer’s relationship satisfaction and commitment: A theoretical model - M. Goaill, Majid; Perumal, Selvan; Mohd Noor, Nor Azila (2013)
Many recent studies emphasized the importance of retailer's satisfaction and commitment to manufacturer/supplier.These studies investigated the relationship between them as an overall relationship. However, there is a dearth of studies that investigated the dimensions of retailer's satisfaction on commitment, and analyzed the mysterious relationship via strength of manufacturer's brands as a moderating effect. Therefore, this study is an attempt to provide a value conceptual model that explains the theoretical linkages existing between dimensions of retailer's satisfaction and commitment, and tries to explain the in - depth meaning of this relationship through the moderating effect of manufacturer's brand strength in the context of social exchange theory. Additionally, hypotheses on the association between the constructs are presented as a basis for further study.